Fifty years of the British journal of learning disabilities: The power of the past. (6th May 2022) - Davies, Ian; Iriate, Edurne Garcia; Jarrett, Simon; Johnson, Kelley; Stainton, Tim; Tilley, Liz; Walmsley, Jan
Accessible summary: This special issue of the journal celebrates the 50th birthday of the British Journal of Learning Disabilities ( BJLD ). The stories in this special issue are about the history of learning disability from around the world. It is important that people know about the history of learning disability, because people with learning disabilities have been kept in the dark for too long. Ian Davies says "why should we be forgotten? We're as much a part of society as everyone else". Over the years BJLD has included stories about learning disability history, but many of these stories were written by people who do not have learning disabilities. In the past few years, people with learning disabilities have been doing important history projects. In this special issue, we have included stories about history that have been written by people with learning disabilities. In the next 50 years, it needs to be easier for people with learning disabilities to write for journals like BJLD . It should also be easier for people with learning disabilities to find out about other people's research in journals like BJLD .